Prevalence & experience of contact with traditional healers among patients with first-episode psychosis in Hospital Kuala Lumpur. - Phang , Cheng Kar; Midin, Marhani; Abdul Aziz, Salina (Malaysian Psychiatric Association, 2010)
Introduction: Patients with mental disorders in Malaysia often seek help from traditional healers prior to consulting psychiatric service. The objective of the study is to determine the prevalence and experience of contact with traditional healers among patients with first-episode psychosis in Hospital Kuala Lumpur (HKL).